THE LINGUOCULTURAL APPROACH TO THE STUDY OF LINGUISTIC PHENOMENA - Abdujalilov Ma'rufjon Islom o’g’li; Nuritdinov Shuxrat Baxirovich (American Journals Publishing, 2023)
The article defines the concept of a linguoculturological approach to the study of linguistic phenomena and the importance of comparing the phraseological pictures of the world of peoples, which is based on the study of the thematic and ideographic semantics of phraseological units and identifying their figurative and motivational foundations, cultural sources for the formation of their semantics. A comparative study of phraseological units allows you to decide a number of complex and still not unambiguously resolved issues of identifying interlingual identities and differences between the two languages - Russian and Uzbek. A significant commonality of the Eurasian way of life, the ever-increasing cultural and economic ties between Russia and Uzbekistan are reflected in the phraseology of the two compared languages. The study of the essence of the language makes it possible to better understand the spiritual heritage, rich history, national values, cultural and spiritual wealth of any people.
Keywords: linguoculturology, toretic-methodological base, cultural and national specificity, thematic-ideographic semantics, emotional coloring, figurative-situational motivation, complex analysis.